Bocconia cultivation in the Belgorodsky region - Zh. M. Yakhtanigova; I. V. Kulishova; A. V. Afanasiev; V. I. Sidelnikov (Новые технологии, 2022)
Bocconia is an evergreen plant belonging to the poppy family, and has been used in folk medicine since ancient times. The unique feature of plume poppy to cure various diseases can be explained by the alkaloids, sanguinarin and heleritrin, available in its green component. In the period of 2019 – 2021 in the Belgorod branch of the federal state budgetary scientific institution «All-Russian Institute of medicinal and aromatic plants» field studies were carried out to study the effect of AgroMaster complex fertilizer of grade 13-40-13 with microelements on the productivity of plume poppy. Complex fertilizers are an important reserve for increasing the productivity of crops, including medicinal and aromatic plants [4, p. 273]. Along with the main application of mineral fertilizers, a significant role belongs to plant fertilization, especially complex fertilizers with trace elements. The main components of complex fertilizers are macrofertilizers (nitrogen, phosphorus, potassium, and others), which are necessary for proper growth and development of any crops. Auxiliary composition of complex fertilizers includes such important chemical elements as zinc, copper, manganese, and others. All of the above makes the use of complex fertilizers an indispensable method of increasing the productivity of cultivated crops [6, p. 194; 7, p. 138; 11, p. 55]. The objectives of the study are to study the peculiarities of adaptation, growth processes and yields of bocconia in specific agro-ecological conditions. Variants of field study included different doses of AgroMaster 13-40-13 fertilizer (from 2 to 5 kg/ha) with single and double treatment of plants to identify the optimal value. The greatest intensity of growth processes, as well as the growth of leafy mass has been found in the double treatment of plants at a dose of 2.0 + 2.0 kg/ha. Variant with maximum dose of fertilizer is 5,0 kg/ha at double treatment provided insignificant yield increase – 0,1 t/ ha against the background of the best variant.